Cruise port centrality and spatial patterns of cruise shipping in the Asian market - Jeon, Jun-Woo (2021)
This paper investigates the centrality of cruise ports in the Asian cruise shipping market while proposing the hubs and authorities centrality (HACC) metric as a directional synthesis of the hubs centrality and authorities centrality to explore cyclical and directional features of centrality in the cruise shipping network. With the development of the cruise shipping industry, research has been actively conducted with a particular focus on identifying the characteristics of hub ports. This paper employs social network analysis to investigate the HACC which is originally developed for analyzing the cruise port centrality problem. Empirical study implies that Ho Chi Minh City, Hong Kong, Nagasaki, Penang, Phuket, Port Klang, Shanghai, and Singapore (in alphabetical order) reflects particulars of cruise hub ports. One of the exceptional results of this paper is Ho Chi Minh City, Penang, Phuket, and Port Klang have demonstrated high HACC (refers to hub ports) while limited degree and betweenness centrality. In contrast, Busan and Keelung are not classified as hub ports.